2015
DOI: 10.1371/journal.pone.0128515
|View full text |Cite
|
Sign up to set email alerts
|

A Difference in Fatty Acid Composition of Isocaloric High-Fat Diets Alters Metabolic Flexibility in Male C57BL/6JOlaHsd Mice

Abstract: Poly-unsaturated fatty acids (PUFAs) are considered to be healthier than saturated fatty acids (SFAs), but others postulate that especially the ratio of omega-6 to omega-3 PUFAs (n6/n3 ratio) determines health. Health can be determined with biomarkers, but functional health status is likely better reflected by challenge tests that assess metabolic flexibility. The aim of this study was to determine the effect of high-fat diets with different fatty acid compositions, but similar n6/n3 ratio, on metabolic flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 70 publications
3
60
1
Order By: Relevance
“…On the other hand, these parameters were not fully deteriorated as, for example, in Ob/Ob mice . Metabolic flexibility is a biomarker for metabolic health that can be assessed non‐invasively using indirect calorimetry . Using a fast‐refeeding challenge, we here found a dose‐response effect, showing that mice fed 30 mg NR/kg diet (30NR) were more metabolically flexible than the wide range of other NR concentrations.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…On the other hand, these parameters were not fully deteriorated as, for example, in Ob/Ob mice . Metabolic flexibility is a biomarker for metabolic health that can be assessed non‐invasively using indirect calorimetry . Using a fast‐refeeding challenge, we here found a dose‐response effect, showing that mice fed 30 mg NR/kg diet (30NR) were more metabolically flexible than the wide range of other NR concentrations.…”
Section: Discussionmentioning
confidence: 70%
“…The metabolic health effects of NR as an exclusive source of vitamin B3 at nutritional relevant levels are unknown. Recently, the ability to rapidly switch metabolism between carbohydrate oxidation and fatty acid oxidation, so‐called metabolic flexibility, has been recognized as a sensitive biomarker for metabolic health in nutritional interventions . Metabolic flexibility can be assessed by analysing the respiratory exchange ratio (RER) during a fast‐refeeding challenge in non‐invasive indirect calorimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some studies investigating the effects of dietary fat on rodent cardiac functions, most of them do not report specific FA profiles or do so only for total lipid FA profiles in heart tissue [50,53,72]. Alternatively, only FA profiles for one selected group of lipid species are presented [86][87][88]. Some studies focused mostly on SFAs and MUFAs [51], while PUFAs have not been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…In week 11, OGTT analyses were performed as previously published, with minor modifications. Briefly, food was removed 1 h after start of the light phase.…”
Section: Methodsmentioning
confidence: 99%